2011
DOI: 10.1037/a0023686
|View full text |Cite
|
Sign up to set email alerts
|

Language and the bicultural dialectical self.

Abstract: We examined the effect of language priming on naïve dialecticism, with special attention paid to effects on dialectical beliefs about the self. European Americans responding in English and bilingual Chinese responding in either Chinese or English completed several measures designed to tap dialectical thinking and dialectical self-perceptions, including tolerance of contradiction, change in thoughts and behavior over time and context, holistic beliefs, and self-concept inconsistency. As expected, those answerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In another study, Chinese‐English bilinguals were randomly assigned to complete measures in either Chinese or English. Consistent with the cross‐national differences reported earlier, Chinese respondents were more likely to agree that contradictory traits described themselves than those responding in English (Boucher & O’Dowd, 2009).…”
Section: Understanding East Asian‐western Differences and Similaritiesupporting
confidence: 85%
See 1 more Smart Citation
“…In another study, Chinese‐English bilinguals were randomly assigned to complete measures in either Chinese or English. Consistent with the cross‐national differences reported earlier, Chinese respondents were more likely to agree that contradictory traits described themselves than those responding in English (Boucher & O’Dowd, 2009).…”
Section: Understanding East Asian‐western Differences and Similaritiesupporting
confidence: 85%
“…For example, when Chinese were primed to think dialectically, there was no effect on positive self‐esteem scores, relative to a control group; however, negative self‐esteem was lower for the dialectical group (Spencer‐Rodgers et al., 2004). Chinese‐English bilinguals responding in Chinese reported more negative self‐esteem than those responding in English, although their positive self‐esteem was similar (Boucher & O’Dowd, 2009). In research using a conceptual relative of the IAT, Boucher, Peng, Shi, and Wang (2009) found that while Chinese, Chinese‐Americans, and European‐Americans were equally efficient at associating self with positive valence, Chinese were better at associating themselves with negative valence than the other groups.…”
Section: Understanding East Asian‐western Differences and Similaritiementioning
confidence: 99%
“…Therefore, the present research seeks to examine how using an East Asian language activates dialectical thinking and drives individuals' attention to perceiving more differences and discrepancies in their own and others' traits, as well as perceiving more variability and inconsistency in their behavior during social interactions. Boucher and O'Dowd (2011) found language priming effects on dialecticism, using samples of European Americans and bilingual Chinese Americans. Bilinguals who answered questionnaires in Chinese scored higher in dialectical thinking, tolerance for contradiction, changing behavior over time and context, holistic thinking, and self-concept inconsistency.…”
Section: Culture and Cognitive Stylementioning
confidence: 93%
“…Boucher and O'Dowd () found language priming effects on dialecticism, using samples of European Americans and bilingual Chinese Americans. Bilinguals who answered questionnaires in Chinese scored higher in dialectical thinking, tolerance for contradiction, changing behavior over time and context, holistic thinking, and self‐concept inconsistency.…”
Section: Language Use and Culturementioning
confidence: 99%
“…This finding is inconsistent with previous research on cultural mindsets and language use among bilinguals. According to previous studies, cultural cues in social contexts and environment would prime bilingual individual's cultural mindset, which leads to distinctive response patterns in ways of thinking, self-concept, personality, and emotion expression (Benez-Martínez et al, 2002;Boucher & O'Dowd, 2011;Chen & Bond, 2010;Chen et al, 2014;Lee et al, 2010;Oyserman & Lee, 2008;Trafimow et al,1997).…”
Section: Description Of Language Cultural and Sexual Variablesmentioning
confidence: 99%